Associativity and social capital in the multicultural context of Chilean migration 2014-2017 Social networks in the immigrant response? - Torreblanca Urzúa, Alexis (AWARI, 2020)
This article discusses Putnam’s (2007) proposal about the possibility that intercultural heterogeneity may negatively affect social capital creation in the short term while also negatively affecting associativity. This issue will be discussed in relation to the case of collective political action by migrant organizations, namely MovimientoAcciónMigrante (MAM) and Coordinadora Nacional de Inmigrantes (CNI) in Chile during the 2014-2017 period. From a social network perspective, this article describes the context of the Chilean socio-political integration model, by both characterizing these groups and exploring the existence of—or lack thereof—politicization and social capital. This exercise seeks to elucidate whether these groups may or may not be considered social networks. By using a mixed-methods approach that included interviews and social network analysis techniques, the researchers accounted for here explores the question: Which are the politicization strategies used by socio-political networks composed by multicultural migrant organizations in the Chilean public sphere? From a combined perspective of political science and network analysis, this article addresses politicization and collective action of these collectives in Chile.